The structure of reduced potential performance model in ski jumping - Jost, B.; Tusak, M. (Journal of Human Kinetics, 2002)
The purpose of this study was to establish on a sample of 50 best Slovene ski jumpers the structure of reduced model of potential performance in ski jumping by means of a decision expert system called "Sport Expert - SPEX". In the first phase, a model of the so-called competition and potential performance was constructed. Thus, elementary and derived morphological-motor and psychological variables were included into the model of potential performance. The two subspaces of the variables, both, the morphological-motor and the psychological, were statistically significantly correlated with the competition performance of ski jumpers in the 1997/98 season (Mult R=.76, Rsq R=.58, Sig F=.00). Using the selected variables it was possible to explain 46% of the performance variance within the morphologicalmotor space (Mult R=.68, Rsq R=.46, Sif F=.00), and 51% of the performance variance within the psychological subspace (Mult R=.71, Rsq R=.51, Sig F=0.00). The contribution of the psychological space to the formation of a common regression equation - in whose formation of transformed values of morphological-motor and psychological spaces was used - was slightly larger (Beta=0.44).